E-079 Middle meningeal artery embolization associated with reduction in chronic subdural hematoma volume and midline shift reduction in the acute post-operative period. (23rd July 2022) - Catapano, J; Hanalioglu, S; Farhadi, D; Tunc, O; Naik, A; Winkler, E; Srinivasan, V; Koester, S; Lawton, M; Jadhav, A; Ducruet, A; Albuquerque, F
Abstract : Background: Chronic subdural hematomas (cSDH) are associated with significant morbidity and high rates of recurrence, and effective management is essential to reducing the disease burden. Middle meningeal artery (MMA) embolization is a minimally invasive treatment strategy which is growing in popularity. We sought to evaluate whether hematoma volume and midline shift were reduced in the immediate post-operative window (<24h) following embolization. Methods: We performed a retrospective analysis of 81 unique patients with 98 chronic subdural hematomas managed via MMA embolization. SDH volumes and midline shift were quantified through image segmentation pre- and post-operatively (24-hour post-procedure) through computed tomography (CT) scans. Other demographic, clinical and operative parameters were abstracted from the medical record in a subset of patients for multivariate analysis. Paired t-tests were used to determine significant reduction in midline shift and SDH volume. Multivariate analysis was performed using logistic and linear regression for percent improvement from baseline volume. Results: Across 81 patients and 98 cSDHs, the mean initial SDH volume was 66.54 mL (SD: 34.67 mL), with the mean midline shift as 3.79 mm (SD: 2.85 mm). There was a significant mean reduction in SDH volume post-operatively (12.1 mL (95% CI: 9.32 - 14.27 mL), p < 0.001). There was also a significant mean reduction in midline shift (0.8 mm (95% CI: 0.24 - 1.36 mm), p = 0.006). 22% of patients had a reduction of over 30% in the immediate post-operative period. A multivariate analysis of 36 patients was performed. There were no significant parameters observed influencing degree of reduction. Discussion: MMA embolization is a safe, and effective approach for the management of cSDH patients. We show a significant reduction of hematoma volume and reduction of midline shift even in the acute post-operative period. Larger studies, randomized trials, and longer-term studies are needed to confirm these findings. Disclosures: J. Catapano: None. S. Hanalioglu, : None. D. Farhadi: None. O. Tunc: None. A. Naik: None. E. Winkler: None. V. Srinivasan: None. S. Koester: None. M. Lawton: None. A. Jadhav: None. A. Ducruet: None. F. Albuquerque: None.